Animals, Humans and Sociability - Tedeschi, Enrica (Italian Sociological Review, 2016)
This article discusses animal studies from the point of view of sociability as an “inter-subjective field of action” and as an agent and builder of society (“doing society”). In sociology, the zoological connection has availed of the theory of borders and critical realism, but, above all, of constructionism, in its interactionist and ethno-methodological sense and both focused on social micro-interaction. The construction of the identity of social actors (both human and animal) is especially evident in interaction regarding play, games, sport, daily life and work. In these spheres, analyses shed light on ambivalent and contradictory human experiences that clash with the dominant culture, while highlighting practical resistance against speciesism, which it is well worth to bring to the attention of future research, using open, mixed methodologies.